Feasibility of substituting soda pulping with high consistency kneaded chemi mechanical pulping for discarded oyster farming bamboo scaffolding - Hao-Chen Sun; Yu-Hsun Lai; Yu-Jia Lo; Kuan-Yeh Huang; Ssu-Yu Huang; Jiann-Gwo Shyu; Yuan-Shing Perng (Scientific Reports)
Abstract In the previous study, discarded oyster farming bamboo scaffolding (BS) demonstrated the potential for application in pulping and papermaking through the soda pulping process. However, soda pulping involves high temperatures and chemical dosages. Therefore, this study develops an alternative pulping process to lower temperature and chemical demands by utilizing a high-consistency kneader (HCK), simultaneously promoting the utilization of BS in pulping and papermaking. This study applies a factorial experimental design to assess the impact of thermo-alkali pretreating conditions (temperature and NaOH dosage) by analyzing pulping yield, freeness, fiber appearance, and handsheet properties. The factorial analysis shows that the temperature and NaOH dosage of thermo-alkali pretreatment significantly affect the pulp properties. The optimal condition of 125℃ and 7.5% NaOH dosage has the highest accepts ratio, the best refining capacity, and the highest handsheet strength. Further compared with previous soda pulping research, utilizing HCK can produce similar pulp properties while increasing the pulping yield and reducing the temperature (-26.5%) and chemical demands (-46.4%). In summary, HCK demonstrates feasibility and potential for application in the pulping process, offering a new perspective on mechanical pulping as presented in this study, while also creating an opportunity to promote BS utilization.